Phytochemical, Antibacterial and Antioxidant Activities of Schefflera elliptica Leaves - I Gede Yoga Ayuning Kirtanayasa; Anak Agung Gede Indraningrat; I Putu Candra (Biology, Medicine, & Natural Product Chemistry, 2023)
Schefflera elliptica or locally called kayu tulak, is one of the Balinese herbal plants that have traditionally be used to reject (tulak) negative influences that exist in the human body. Althoug, S. elliptica has been routinely used as a part of a ritual in Bali, only a limited study has been reported on its bioactivity. This study was designed to analyze the phytochemical content, antibacterial activity, and antioxidant activity of S. elliptica. In this study, simplisia of S. elliptica was extracted using n-hexane and ethyl acetate solvents, then the viscous extracts of the two solvents were carried out for phytochemical tests, antibacterial activity tests with the Kirby-Bauer method and antioxidant activity tests with based on DPPH method. Phytochemical screening showed that the n-hexane extract contains active compounds in the form of phenols and steroids while ethyl acetate contains active compounds in the form of phenols, tannins, and steroids. Antibacterial screening showed ethyl acetate extract of S. elliptica displayed a diameter zone of inhibition of 10.720.71 mm against Staphylococcus aureus, 12.172.80 mm against Streptococcus mutans, 12.401.65 mm against Escherichia coli and 15.202.44 mm against Klebsiella pneumoniae. The DPPH analysis showed percentages of 61.17% and 67.42% from n-hexane and ethyl acetate extracts respectively, which indicated the antioxidant properties of S. elliptica. Overall, this research provides a preliminary report on the bioactivity potential of S. elliptica mainly in term of antibacterial and antioxidant properties which open up possibilities for future drug development.